Clinical Profile of Episodic Wheezing and Multiple Trigger Wheezing in Preschool Children: A Cross-Sectional Study - Tualzik, Lalsiama; Chandrasekaran, Venkatesh (Journal of Child Science, 2020)
The objectives of our study were to identify the relative frequency of episodic viral wheeze (EVW) and multiple trigger wheeze (MTW) in preschool children of 1 to 5 years of age with recurrent wheezing and to compare the relevant clinical and sociodemographic parameters in the above phenotypes. This cross-sectional study included 165 children aged 1 to 5 years with recurrent wheeze. Participants were categorized into EVW and MTW based on history according to European Respiratory Society Task Force recommendations 2008. Symptom control was assessed by Global Initiative for Asthma guidelines 2015. Of the total participants, EVW was seen in 55% and MTW in 45%. Children with MTW were significantly older than those with EVW, more atopic, and had higher eosinophil counts. The dominant phenotype seen in our study was EVW. The absence of ocular/nasal allergy and exclusive breastfeeding predicted well-controlled symptoms in EVW and in all preschool wheezers, respectively.
Keywords: atopy; children; EVW; MTW; phenotype; preschool; wheeze